MOVPE Growth of Smooth and Homogeneous Al0.8Ga0.2N:Si Superlattices as UVC Laser Cladding Layers. Issue 13 (26th April 2018) - Kuhn, Christian; Simoneit, Tino; Martens, Martin; Markurt, Toni; Enslin, Johannes; Mehnke, Frank; Bellmann, Konrad; Schulz, Tobias; Albrecht, Martin; Wernicke, Tim; Kneissl, Michael
Abstract : Smooth, uniform, and conductive Alx Ga1−x N layers with high aluminum mole fractions of x  > 0.7 are required as cladding layers for laser diodes emitting in the deep ultraviolet spectral region. In this paper, the growth of silicon‐doped AlGaN/AlGaN superlattices by metal‐organic vapor phase epitaxy is investigated and compared to bulk AlGaN layers. It is found that the superlattice approach enables the growth of AlGaN layers with improved lateral uniformity of composition and strain state. In order to reduce the surface roughness, growth interruptions between the superlattice layers are investigated. With increasing growth interruption time, the average aluminum content is increasing and the superlattice period thickness is decreasing. Scanning transmission electron microscopy investigations show that the growth interruptions lead to more abrupt interfaces and to the formation of one to two monolayer thin aluminum‐rich AlGaN layers at each interface. This also leads to a significantly smoother surface morphology. Low resistivities of 0.025 Ω cm are obtained for AlGaN:Si superlattices with average aluminum content of x  = 0.8. The influence of the surface morphology of the AlGaN cladding layers on optically pumped laser heterostructures is investigated. By using a smooth AlGaN superlattice, the lasing threshold decreases by a factor of 2 compared to lasers with bulk AlGaN cladding layers. Abstract : Smooth, uniform and conductive AlGaN layers are required as cladding for deep UV laser diodes. The MOVPE growth of Al0.8 Ga0.2 N:Si superlattices with growth interruptions is investigated and compared to bulk AlGaN layers. Superlattices enable much smoother morphologies and structural homogeneity. Furthermore, by using superlattice cladding layers in laser heterostructures, the lasing threshold in optical pumping experiments decreases almost by a factor of 2 compared to lasers with bulk AlGaN cladding.